2010
DOI: 10.4996/fireecology.0603045
|View full text |Cite
|
Sign up to set email alerts
|

Historic Fire Regime of an Upland Oak Forest in South-Central North America

Abstract: Prescribed burning is used in upland oak forests of south-central North America to improve wildlife habitat, reduce fire hazard, restore ecosystem integrity, and maintain biological diversity. However, little is known about the frequency, seasonality, and ignition source of historic fires that shaped these forests. In general, it is believed that fire frequency in upland oak forests of south-central North America was influenced by climate and humans, and decreased since Euro-American settlement; yet there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…4). This result is similar to other studies in the Oklahoma Cross Timbers (Allen and Palmer 2011;DeSantis et al 2010b;Stambaugh et al 2009) and contrary to that reported by Clark et al (2007). Three of four severe fire years (1898,1912,1955) coincided with below average PDSI (drought) conditions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…4). This result is similar to other studies in the Oklahoma Cross Timbers (Allen and Palmer 2011;DeSantis et al 2010b;Stambaugh et al 2009) and contrary to that reported by Clark et al (2007). Three of four severe fire years (1898,1912,1955) coincided with below average PDSI (drought) conditions.…”
Section: Discussionsupporting
confidence: 84%
“…DeSantis et al (2010b) Stambaugh et al (2013) found a fire frequency of 2.6 years in a mixed oak-pine (Quercus-Pinus) forest. Masters et al (1995) in a study of fire history in McCurtain County reported a mean fire interval of 3.8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the historical fire return interval pre-European American settlement ranged from 2.9-6.7 years [4][5][6][7][8]. Due to a combination of fire exclusion and favorable recruitment Once the forest areas were identified on each of the 25 properties [20], five field measurement plots per property (one larger property had ten field measurement plots) were randomly located within the forest interior using ArcMAP (Esri, Redlands, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…During the Holocene, increasing fire occurrence, often due to Native American land use practices, favored the dominance of oak-pine (Quercus/Pinus) natural communities such as forests, woodlands, and savannas in North America [5][6][7][8]. In historic times, fire frequency was highest in the oak region during the early European settlement period [9][10][11] when settlers saturated the landscape with fire and initiated a wave of fire that rolled from the eastern seaboard to the tallgrass prairies [12,13]. Widespread catastrophic fires, which burned in logging slash circa the 1850s to 1920s, caused severe destruction on millions of acres and took thousands of lives, bringing the need for wildfire control to national attention.…”
Section: Introductionmentioning
confidence: 99%